Gestión de proyectos y participación ciudadana en la gestión municipal de la Municipalidad Provincial de Lucanas - Rivas Moreano, Ana Beatriz (2022)
Citizen participation is an issue promoted and disseminated by public entities and various organizations that defend this right, however, it is the citizens who have lost interest in project management and the closest thing to it is municipal management, this is due to to the existence of shortcomings in technical support and ignorance in various requirements, INEI (2020). This research aims to propose a proposal in relation to strengthening the capacities of citizens in the projects to be implemented in order to improve municipal management. Non-experimental quantitative research was carried out, with three variables, a sample of 128 inhabitants, with simple random sampling. The results found are, 55.5% present an average level in terms of perception in the management of projects executed by the Municipality, citizen participation was 59.4% average level and 58.6% perceive municipal management at an average level, it is shown that there is a low perception of the inhabitants regarding the perception of the variables. Lastly, we consider that the exercise of citizenship with a focus on the implementation of projects contributes to democracy and good governance.